PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP RASA BERSYUKUR SISWA SMP IT YASPIDA SUKABUMI - Kurahman, Opik Taupik; Muttaqin, Via Putrimawati (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
Gratitude is an affective dimension that should be embedded in every student. So Ibn Khaldun outlined that the affective aspect (khuluqiyyah) is change which includes awareness, feelings and mental attitudes. Among these changes is the manifestation of mahmudah (good) qualities. As servants of Allah, humans, in this case students, must be grateful to Allah SWT. as explained in the Qur'an regarding Allah's appreciation for grateful humans in QS. Ibrahim: 7. The use of learning media is an attraction in itself and a motivation for learning. In previous research, researchers found students' enthusiastic attitudes when learning using learning media.  As in the realm of affection, it is not only presented theoretically, but is accompanied by concrete examples so that the meaning can be appreciated and then reflected in one's mental life. So, with this high level of enthusiasm in using learning media, does it also give rise to a mental awareness of gratitude in IT Yaspida Middle School students, as a form of instilling affectional values ​​to become a reference and contribute to the novelty of Islamic educational knowledge. The objectives of this article are: 1) Knowing what is meant by learning media; 2) Know what is meant by students' gratitude; 3) Knowing the effect of using learning media on students' feelings of gratitude. The methodology used is a quantitative regression approach which not only connects the two variables, but also finds out the influence of both. From the calculation stage carried out to obtain the decision results, it is known that the calculated t value is 5.066 > t table 2.042, so the results of this research are that Ha is accepted and H0 is rejected, with supporting analysis of the coefficient of determination (R Square) of 0.461 which shows that there is a positive influence between the independent variables ( learning media) on the attachment variable (feeling of gratitude) of 46.1%. This means that there is a positive influence between learning media (X) and students' feelings of gratitude (Y).